Six Sigma methodology for loss reduction in soybean transfer in a grain beneficiary unit - Chiroli, Daiane Maria De Genaro (2019)
With globalization and increased commercial competitiveness, the search for better results as well as efficient processes has been a crucial factor in ensuring good performance and competitiveness for companies. Thus, in order to avoid waste and safety, the better performance of the production processes, methods such as Six Sigma are used, so that they are identified as the main productive losses, eliminating waste. The purpose of this paper is to deploy a Six Sigma tool to identify and eliminate waste in the transfer between the bulk carrier and an agroindustrial cooperative factory. The Six Sigma methodology was used, based on the DMAIC (Define, Measure, Analyze, Improve Control) tool to measure and analyze the main losses of the process, proposing improvements and solutions to minimize homelessness in the process of receiving, storing and transportation of the soybean grain, from the bulk carrier sector to the oil extraction sector. A major contribution of the Six Sigma project to an analysis and knowledge of the soybean transfer process, and of each productive stage. Through this project, it was possible the great involvement of the employees, who contributed in the various stages carried out and sought improvement and greater knowledge of all the present stages, as well as the establishment of standards in the activities.